O uso de maquetes no ensino de Ciências - LIMA, Viviane Sousa de (2024)
The didactic materials are tools that facilitate the Sciences teaching and are characterized as important resource to assist in the teaching and learning process, because support the add to knowledge by students. This way, was plan, prepare and make use of mockup in the class to preparing students for a school science fair, whose participation it would be evaluation of the Sciences discipline. The mockup were be made about the origin and evolution of the universe, the primitive earth and the internal layers of the earth, of the thematic unit earth and the universe. Based on the use of this material, I describe the teaching-learning opportunities that arose during the process of building and using the mockups, as well as reflections on the importance of this experience in my teacher construction. The results obtained indicated that the use of mockups contributed to the process of multiple learnings, the students they were able to demonstrate mastery in the knowledge about contents, were very participative, lost their shyness, learned to work as a team and, mainly, developed the orality. This experience gave me the opportunity to plan, search for information, and better relationship ties with students, as well as making me rethink for my teaching practice and the possibility of using different teaching strategies.